Tracing the Evolutionary Pathways of Serogroup O78 Avian Pathogenic Escherichia coli - Eun-Jin Ha; Seung-Min Hong; Seung-Ji Kim; Sun-Min Ahn; Ho-Won Kim; Kang-Seuk Choi; Hyuk-Joon Kwon (MDPI AG, 2023)
Avian pathogenic E. coli (APEC) causes severe economic losses in the poultry industry, and O78 serogroup APEC strains are prevalent in chickens. In this study, we aimed to understand the evolutionary pathways and relationships between O78 APEC and other E. coli strains. To trace these evolutionary pathways, we classified 3101 E. coli strains into 306 subgenotypes according to the numbers and types of single nucleotide polymorphisms (RST0 to RST63-1) relative to the consensus sequence (RST0) of the RNA polymerase beta subunit gene and performed network analysis. The E. coli strains showed four apparently different evolutionary pathways (I-1, I-2, I-3, and II). The thirty-two Korean O78 APEC strains tested in this study were classified into RST4-4 (45.2%), RST3-1 (32.3%), RST21-1 (12.9%), RST4-5 (3.2%), RST5-1 (3.2%), and RST12-6 (3.2%), and all RSTs except RST21-1 (I-2) may have evolved through the same evolutionary pathway (I-1). A comparative genomic study revealed the highest relatedness between O78 strains of the same RST in terms of genome sequence coverage/identity and the spacer sequences of CRISPRs. The early-appearing RST3-1 and RST4-4 prevalence among O78 APEC strains may reflect the early settlement of O78 E. coli in chickens, after which these bacteria accumulated virulence and antibiotic resistance genes to become APEC strains. The zoonotic risk of the conventional O78 APEC strains is low at present, but the appearance of genetically distinct and multiple virulence gene-bearing RST21-1 O78 APEC strains may alert us to a need to evaluate their virulence in chickens as well as their zoonotic risk.